A critical analysis of the representation of Yemen crisis in ideologically-loaded newspaper headlines - Abdi, Reza; Basarati, Ali (Penerbit Universiti Kebangsaan Malaysia, 2016)
This qualitative research is a critical discourse analysis of the representation of Yemen crisis in ideologically-inclined newspaper headlines of Iran, Arab and the West. A total of 63 headlines were selected as the corpus of this study. The newspapers included Iran Daily, Tehran Times, Iran on-line and IRNA (Islamic republic news agency) from Iranian; Al-sharq Alwsat and Al-Jazeera from Arab; and finally Telegraph, USA Today, News Week, and New York Time from among the Western newspapers. The three dimensional model of Norman Fairclough was employed to explore the specific themes conveyed through the representation of participants and processes about Yemen crisis. The findings showed that the Houthis are introduced as rebels by both Arab and Western newspapers, and that Saudi Arabia plays a protective role against rebels. On the other end, Iran, along with representing Saudis and the westerns as intruders, chooses and promotes a diplomatic way by condemning the military measures and inviting the parties to come up with a diplomatic solution. Meanwhile, the West supports Saudi-led coalition and legitimates Saudi’s attack by proving that the Houthis are Rebels. As for the source of such opposing discourses, it is argued that the opposing ideological views of Islam in the Middle East and the discourse of Secularism in the West lead to contradictory discourses in the region.